ANTIBACTERIAL AGENTS FOR THE CREATION OF TEXTILE MATERIALS – CURRENT STATE AND TRENDS DEVELOPMENT - ВАРДАНЯН, АННА; REDKO, YANA (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Antibacterial textiles refer to a range of special-purpose textile materials that provide products with such an important functional characteristic as protection against pathogenic microorganisms by inhibiting their growth or completely neutralizing their impact on humans. Such materials are used in a variety of areas, ranging from household to commercial, including air filters, food packaging, healthcare, hygiene, medicine, sportswear, storage systems, ventilation and purification systems. This paper investigates the relevance of the chosen direction by determining the interest in antibacterial agents for the antibacterial treatment of textile materials, as well as identifying their current functional perspective and future opportunities. The areas of application of triclosan as a broad-spectrum antibacterial agent are presented. The bibliometric analysis of publications of triclosan-containing commercial products, namely: "Irgaguard®", "Irgasan®", "Tinosan®" and "Microban®", which were used as keywords for search queries in Google Scholar. Among the four industrial names of triclosan, "Irgasan®" was the most mentioned among the global scientific community in terms of scientific publications. Statistical data on the interest in the industrial names of antibacterial agents among users of the Google search engine we obtained using the Google Trends system. The reasons for the increase and decrease in interest in antibacterial agents over the past five years among potential consumers and the scientific community are analyzed in accordance with the number of articles and search queries. This study focuses on the increase in demand in the scientific field since the beginning of 2020. The greatest interest among consumers in antibacterial agents is identified directly during the outbreaks of the COVID-19 coronavirus disease. It is noted that such triclosan-containing industrial products as Irgaguard®, Irgasan®, Tinosan® had a consistently high interest among consumers compared to the industrial product Microban®. The relevance of this topic is substantiated and the emphasis is placed on the need for development in the direction of approbation and cooperation between industry and scientists to create high-quality textile products with antibacterial properties.
Keywords: triclosan; bibliometric analysis; interest analysis; antibacterial agent; textile materials